2008
DOI: 10.4103/0970-4388.40316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of allele frequency for HLA-DR and HLA-DQ between patients with ECC and caries-free children

Abstract: The above results suggest that HLA-DRB1*04 is associated with the susceptibility to ECC. Thus HLA-DRB1*04 detection as a molecular marker for early diagnosis of ECC may be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
0
22
0
4
Order By: Relevance
“…However, it did not provide high resolution genotyping as the antigens tested were determined by immunological reactions and not direct DNA sequencing. Bagherian et al [2008] also reported that the DR4-positive subjects younger than 5 years were 10 times more likely to develop early childhood caries than their negative counterparts. In the same way, Yildiz et al [2009] found that HLA-DRB1 * 04 and -DRB1 * 07 frequencies were significantly higher in the DMFT 6 1 group as compared with the DMFT = 0 group.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, it did not provide high resolution genotyping as the antigens tested were determined by immunological reactions and not direct DNA sequencing. Bagherian et al [2008] also reported that the DR4-positive subjects younger than 5 years were 10 times more likely to develop early childhood caries than their negative counterparts. In the same way, Yildiz et al [2009] found that HLA-DRB1 * 04 and -DRB1 * 07 frequencies were significantly higher in the DMFT 6 1 group as compared with the DMFT = 0 group.…”
Section: Discussionmentioning
confidence: 97%
“…Associations between dental caries and the HLA region were obtained in both animal [Niiyama et al, 1987;Kurihara et al, 1991;Suzuki et al, 1998] and human studies [Lehner et al, 1981;Acton et al, 1999;Altun et al, 2008;Bagherian et al, 2008;Yildiz et al, 2009]. In the study conducted by Lehner et al [1981] the genetic predisposition towards caries was found to be positively associated with HLA-DR4 antigens and negatively with HLA-DRw6-related antigens.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Other authors noticed the genes from MHC complex, especially DR4 and DR3 in persons with a high level of S. mutans in the oral cavity [19]. De Vries et al [20], in turn, discovered no relation between caries incidence and the type of HLA DR.…”
Section: Impact On Host Response To Oral Bacteriamentioning
confidence: 98%